2020
DOI: 10.37934/arfmts.73.1.109130
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Liquefied Petroleum Gas Recovery from Off Gases in a Fuel Oil Refinery

Abstract: With the growing need and demand for petroleum fuels in the industrial, automotive and domestic sectors, it has become the need of time to address this problem. The important question is, what engineers can do in this regard. There is a simple solution to cater this problem, the production trends worldwide are increasing every year, but still, the demand keeps increasing exponentially. One way is to stress emphasis on reducing the wastage of these precious fuels and, at the same time, implement methodologies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It is found that CNG and LPG recovery is the least cost and most profitable alternative for the six different technological options, including gas to hydrate, gas to liquid, combined heat and power generation, and liquefied natural gas (Jokar et al, 2021). An attempt has been made for the process through which LPG can be recovered from the off gases of the fuel oil refinery to meet the demand of petroleum fuel in automotive, industrial, and domestic sectors (Qamar et al, 2020). The integration of the dehydration recovery and natural gas liquid unit tends to increase the LPG profit and capacity (Masnsour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is found that CNG and LPG recovery is the least cost and most profitable alternative for the six different technological options, including gas to hydrate, gas to liquid, combined heat and power generation, and liquefied natural gas (Jokar et al, 2021). An attempt has been made for the process through which LPG can be recovered from the off gases of the fuel oil refinery to meet the demand of petroleum fuel in automotive, industrial, and domestic sectors (Qamar et al, 2020). The integration of the dehydration recovery and natural gas liquid unit tends to increase the LPG profit and capacity (Masnsour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%